Creating A Fuzzy Logic Model for Early Assessment o Payment Problems in Construction Projects In Iraq - A. Al-Asadi, Ibrahim; S. M. Khaled, Zeyad; M.H. Kashkool, Afrah (International Journal of Engineering and Technology, 2018)
The aim of this research is to create a fuzzy logic model that can aid in assessing payment problems encountered in construction projects in Iraq. The model was created based on the findings of a previous study of the authors in which (67) causes of payment problems in construction projects in Iraq were identified. The causes were ranked by (72) professionals from (38) Iraqi firms based on the frequency and severity of causes. All causes were employed in the model after categorizing them in four groups: owner-related, contractor-related, consultant-related and external causes. The model was constructed using MATLAB Program Software Version 2. Finally the model was tested against (10) real life projects and found to be appropriate to aid owners and contractors in the Iraqi Construction Industry to early assess payment problems in order to take preventive actions.Â